Global Entrepreneurship Monitor Caribbean: 2012 Colombian National Report (2013)
A broad agreement exists among the academia and public policy makers about the importance of entrepreneurial activity and entrepreneurs in the dynamics of economic development. New businesses drive innovation, create jobs and, stimulate productivity and competition thereby developing the economy and adding social value.